Applying a Health-Risk Behavior Lens to Understand Individual Differences in COVID-19 Containment Behavior Among Young Adults. Issue 1 (February 2022) - Wallace, Gemma T.; Weishaar, Megan G.; Henry, Kimberly L.; Conner, Bradley T.
COVID-19 containment behaviors (CCBs) remain important methods for reducing contagion. Theoretical frameworks to understand engagement in health-risk behaviors among young people may help identify individuals with elevated risk for non-adherence to CCBs. We aimed to elucidate individual differences in CCBs by evaluating if CCBs fit into an established health-risk behavior framework. Using a cross-sectional sample of 1374 young adults, we examined CCBs' associations with personality antecedents to health-risk behaviors and to actual engagement in other health-risk behaviors. Results identified risk seeking, negative urgency, lack of premeditation, and extraversion as risk factors for less CCB adherence, while agreeableness and neuroticism were protective factors. Less CCB adherence was positively associated with binge drinking, more sexual partners, and risky driving, while negatively associated with purging and self-injury. Results suggest CCBs may be understood as a type of health-risk behavior and can contribute to the development of strategies for increasing public health guideline adherence.